Sustainable Livelihoods in ASALs through Agro-biodiversity: Lessons from Baringo, Kenya - Mwasi, B. N. (Africa Environmental Review Journal, 2015)
It is becoming increasingly difficult for people, especially with arid and semi-arid areas, to meet their socio-economic needs without causing damage to the environment. This is mainly due to increases in population and levels of affluence. This paper discusses how food and other needs in the Baringo area in Kenya can be met on sustainable basis through cultivation and exploitation of biological resources by promoting agrobiodiversity. Cultivation of non-traditional crops such as Aloe vera, Artemisia spp., Azadirachta indica and increased production of honey are examples of such activities. Exploitation of these resources can enhance food security in the area, reduce household poverty, increase access to health and education, thus contributing positively towards achieving the millennium development goals (MDGs). The paper concludes that for this to succeed, there is need for changes in both government policy and socio-cultural values.